The law-governed universe - Roberts, John T. (Oxford : Oxford University Press, 2008)
John T. Roberts measurability account affirms that there is an important sense in which laws govern the universe, rather than simply describing it economically. In this book he argues that what is essential to laws is that they guarantee the reliability of methods of measuring natural quantities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Philosophy of nature; Natural law